The Influence Of Motivation, Career Development, And Self-Efficacy On Employee Performance (Study At Princess Cosmetic Store Banjarmasin) - Damayanti, Maulida Fitri; Nurhayati, Netty; Kurniaty, Kurniaty; Zamilah, Ervica (Islamic University of Kalimantan MAB Banjarmasin, 2025)
This study aims to examine and analyze the influence of: (1) Motivation partially on Employee Performance at Princess Cosmetic Store Banjarmasin, (2) Career Development partially on Employee Performance at Princess Cosmetic Store Banjarmasin, (3) Self-Efficacy partially on Employee Performance at Princess Cosmetic Store Banjarmasin, and (4) Motivation, Career Development, and Self-Efficacy simultaneously on Employee Performance at Princess Cosmetic Store Banjarmasin. This study employs a quantitative research method. The sampling technique used in this study is the saturated sampling technique, with a population comprising all employees of Princess Cosmetic Store Banjarmasin totaling 40 respondents. The data analysis is conducted using Multiple Linear Regression with the SPSS program. The results of this study indicate that: (1) Motivation partially has a positive but not significant effect on Employee Performance at Princess Cosmetic Store Banjarmasin, (2) Career Development partially has a positive and significant effect on Employee Performance at Princess Cosmetic Store Banjarmasin, (3) Self-Efficacy partially has a positive and significant effect on Employee Performance at Princess Cosmetic Store Banjarmasin, and (4) Motivation, Career Development, and Self-Efficacy simultaneously or collectively have a significant effect on Employee Performance at Princess Cosmetic Store Banjarmasin.